Input files for "A phase-shift-periodic parallel boundary condition for low-magnetic-shear scenarios": arXiv 2208.02202 - St-Onge, D (University of Oxford, 2022)
A collection of input files, and instructions on how to use them, for the manuscript entitled 'A novel approach to radially global gyrokinetic simulation using the flux-tube code stella'. These input files, which are designed for the gyrokinetic flux-tube code stella, are specifically for the simulations resulting in figures 2-4.